2013
DOI: 10.1590/s1677-5538.ibju.2013.04.04
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Function after Non-Nerve-Sparing Radical Cystoprostatectomy: A Comparison between Ileal Conduit Urinary Diversion and Orthotopic Ileal Neobladder Substitution

Abstract: Objective: To compare the erectile function (EF) and sexual desire (SD) in men after radical cystoprostatectomy (RCP) who had either an ileal conduit urinary diversion or orthotropic ileal neobladder substitution. Materials and Methods: Eighty one sexually active men with bladder cancer were enrolled in this prospective study. After RCP according to patients' preferences they underwent either ileal conduit urinary diversion (n = 41) or orthotropic ileal neobladder substitution (n = 40). EF and SD were assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 19 publications
0
11
0
4
Order By: Relevance
“…7 The 5-year survival rate of the traditional treatments is 62%, due to the frequent metastasis. 9 Therefore, the primary tasks of improving BCa treatment are to study its pathogenesis and to locate more effective therapeutic targets. 9 Therefore, the primary tasks of improving BCa treatment are to study its pathogenesis and to locate more effective therapeutic targets.…”
Section: Introductionmentioning
confidence: 99%
“…7 The 5-year survival rate of the traditional treatments is 62%, due to the frequent metastasis. 9 Therefore, the primary tasks of improving BCa treatment are to study its pathogenesis and to locate more effective therapeutic targets. 9 Therefore, the primary tasks of improving BCa treatment are to study its pathogenesis and to locate more effective therapeutic targets.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of studies examining sexual function have focused on male patients and predictors and prevalence of sexual function post-RC and ONB reconstruction. Traditionally, erectile function has been reported to be retained in between 24% and 36% of patients post-ONB reconstruction 33,50,51. However, RC approaches with neurovascular bundle preservation may help preserve erectile function.…”
Section: Complications and Patient Outcomesmentioning
confidence: 99%
“…found that men experienced significant deterioration in both erectile function and sexual desire postoperatively, irrespective of the type of urinary diversion performed. [ 26 ]…”
Section: Sexual Functionmentioning
confidence: 99%
“…Between 23.7–35.5% of patients retain adequate erectile function after neobladder reconstruction. [ 15 20 26 ] Some studies demonstrated that neobladder reconstruction results in better preservation of sexual function when compared with an ileal conduit using the International Index of Erectile Function questionnaire. Specifically, 35.0% of men in the ileal neobladder group were able to achieve and maintain erections sufficient for vaginal penetration throughout sexual intercourse, compared with 9.8% of men in the ileal conduit group ( P = 0.006).…”
Section: Sexual Functionmentioning
confidence: 99%
See 1 more Smart Citation